Bilateral Spontaneous Perirenal Hemorrhage in an Acquired Cystic Kidney Disease Hemodialysis Patient - Daigoro Hirohama; Hiroshi Miyakawa (Case Reports in Nephrology)
Acquired cystic kidney disease (ACKD) is a well-known late stage complication of chronic kidney disease. Cysts tend to grow with time on dialysis and could lead to malignant transformation, and intra- or perirenal hemorrhage is a rare complication of ACKD. Here we describe one case of bilateral spontaneous perirenal hemorrhage of ACKD in a 44-year-old man, on hemodialysis for 15 years. One was due to cyst rupture, and the other was due to aneurism rupture, both were controlled with transcatheter arterial embolization. In renal arteriography at the second rupture, we demonstrated extravasation from an aneurysm being present at the periphery of right renal artery. Several spontaneous perirenal hemorrhage cases were reported but its clinical information is limited, moreover, bilateral cases were extremely rare. Furthermore, to our knowledge, this is the first report of spontaneous perirenal hemorrhage caused by intraparenchymal renal artery aneurysm rupture in ACKD patients. We report this case because of its rarity and significance with respect to the complication of dialysis patients, review reported bilateral cases, and discuss some clinical characteristics.